Economic Impact of Extension Interventions on Composite Carp Culture in Dhenkanal and Kandhamal, Odisha - SAHOO, BISWAJIT; Himansu Kumar De,; Abhijit Sinha Mahapatra,; Sushree Sangita Rath, (Indian Journal of Extension Education, 2025)
The aquaculture sector is rapidly growing, significantly contributing to the Indian and global economies by ensuring nutritional security and supporting livelihoods.Composite carp culture is one of the most extensively used technology. The study was carried out in Dhenkanal and Kandhamal districts of Odisha attempts to determine whether composite carp farming is economically viable by examining the costs and benefits of the technology. Data were collected from 220 fish farmers of both Dhenkanal and Kandhamal districrts before and after adoption of Scientific carp culture technology. The total pond area was 3.6 ha in Dhenkanal and 3.7 ha in Kandhamal district. The mean fish yield was 1047.1 kg/ha/yr and rose to 2032.1 kg/ha/yr in Dhenkanal and 1247.2 kg/ha/yr to 2554.5 kg/ha/yr in Kandhamal. Rate of return on total investment (ROI) and Benefit-Cost ratio (B:C ratio) of Dhenkanal and Kandhamal ponds, after intervention was worked out as 124.7%, 1.2 and 169%, 1.7 respectively. Supplementary feed accounted for the largest portion of the cost of fish production, followed by pond leasing value and pond preparation costs. The study suggests that the composite carp culture method is economically viable and has a remarkable benefit-cost ratio.